Dispersions of carbon nanotubes and organomodified clay platelets in cholesteric liquid crystals - Chepikov, A.M.; Minenko, S.S.; Lisetski, L.N.; Lebovka, N.I.; Usol'tseva, N.V.; Soskin, M.S. (Functional Materials, 2012)
Comparative studies were carried out of cholesteric liquid crystal dispersions of anisotropic nanoparticles of different types, namely, essentially rod-like carbon nanotubes (CNT) and plate-like exfoliated particles of organo-modified Laponite and montmorillonite clays. The characteristic properties under study were selective reflection spectra of the cholesteric planar structure and optical transmission changes at the transition temperatures to the isotropic phase. Marked differences were noted in CNT-containing systems for purely steroid matrices and nematic-cholesteric mixtures with nematic 5CB, which presumably reflected differences in CNT interaction with aromatic and non-aromatic molecules. Effects of clay platelets upon selective reflection spectra were much smaller as compared to CNTs, in agreement with our assumption that dispersed plate-like particles should stabilize the planar cholesteric texture. The processes of CNT aggregation were markedly slower in cholesteric matrices as compared with nematics due to higher effective viscosity.